Appraisal of Takagi–sugeno type neuro-fuzzy network system with a modified differential evolution method to predict nonlinear wheel dynamics caused by road irregularities - Taghavifar, Hamid; Motlagh, Asad M.; Mardani, Aref; Hassanpour, Ali; Hosseinloo, Ashkan H.; Taghavifar, Leyla; Wei, Chongfeng (Transport, 2016)
Wheel dynamics play a substantial role in traversing and controlling the vehicle, braking, ride comfort, steering, and maneuvering. The transient wheel dynamics are difficult to be ascertained in tire–obstacle contact condition. To this end, a single-wheel testing rig was utilized in a soil bin facility for provision of a controlled experimental medium. Differently manufactured obstacles (triangular and Gaussian shaped geometries) were employed at different obstacle heights, wheel loads, tire slippages and forward speeds to measure the forces induced at vertical and horizontal directions at tire–obstacle contact interface. A new Takagi–Sugeno type neuro-fuzzy network system with a modified Differential Evolution (DE) method was used to model wheel dynamics caused by road irregularities. DE is a robust optimization technique for complex and stochastic algorithms with ever expanding applications in real-world problems. It was revealed that the new proposed model can be served as a functional alternative to classical modeling tools for the prediction of nonlinear wheel dynamics.